Review of Multidetector Computed Tomography Angiography as a Screening Modality in the Assessment of Blunt Vascular Neck Injuries. Issue 2 (May 2013) - Liang, Teresa; McLaughlin, Patrick D.; Louis, Luck; Nicolaou, Savvas
Blunt vascular neck injuries (BVNI), previously thought to be rare, have demonstrated increasing incidence rates in recent literature and are associated with significant mortality and morbidity. A radiologist needs to efficiently recognize these injuries on preliminary screening to enable initiation of early management. When initiation of accurate management is started promptly, decreased rates of postinjury complications, for example, stroke, have been demonstrated. This article reviews the incidence, pathophysiology, and rationale for screening for these BVNI injuries. The utility of computed tomography angiography (CTA) as the potential new criterion standard as the screening and follow-up imaging modality for BVNI will be discussed. The application of new multidetector CTA techniques available, such as dual-energy CT and iterative reconstruction, are also reviewed. In addition, the characteristic imaging findings on CTA and the associated Denver Grading scale for BVNI will be reviewed to allow readers to become familiar with the injury patterns and to understand the prognostic and clinical implications, respectively. Examples of the spectrum of injuries, potential injury mimics, and different artifacts on multidetector CTA are shown to help familiarize readers and allow them to successfully and confidently recognize a true BVNI.